IMPLEMENTASI DEEP LEARNING DALAM MENINGKATKAN KUALITAS PELATIHAN APARATUR SIPIL NEGARA - Hariandja, Mulya Nanda (Akademika : Jurnal Teknologi Pendidikan, 2025)
This study examines the implementation of a deep learning approach in civil servant (ASN) training at the Bukittinggi Regional PPSDM. Based on a qualitative literature review, the study analyzes the principles of deep learning — conscious , meaningful, and enjoyable—and the learning experience in the form of understanding, application, and reflection. The lack of two-way communication, online fatigue, and limited application of knowledge—which are training challenges—are addressed through a participant-centered learning design supported by project- and problem-based learning strategies. The role of teaching staff as activators , culture builders, and collaborators—supports the success of learning in the training. The results indicate that deep learning is effective in developing ASN competencies, supporting improved performance and quality public services